2022
DOI: 10.1111/brv.12912
|View full text |Cite
|
Sign up to set email alerts
|

Centring individual animals to improve research and citation practices

Abstract: Modern behavioural scientists have come to acknowledge that individual animals may respond differently to the same stimuli and that the quality of welfare and lived experience can affect behavioural responses. However, much of the foundational research in behavioural science lacked awareness of the effect of both welfare and individuality on data, bringing their results into question. This oversight is rarely addressed when citing seminal works as their findings are considered crucial to our understanding of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Studies focusing on laboratory animals were abundant, showing that the concern to improve the welfare of these animals is great since they are often used in biomedical research and the results of such research need to be reliable [ 41 , 42 , 43 ]. Some studies have already shown that low levels of welfare in these animals can generate dubious results in these studies [ 44 , 45 ]. The number of sample individuals used in both farm and laboratory environments is notably higher than in other environments, such as zoos, aquariums, shelters, and pets.…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on laboratory animals were abundant, showing that the concern to improve the welfare of these animals is great since they are often used in biomedical research and the results of such research need to be reliable [ 41 , 42 , 43 ]. Some studies have already shown that low levels of welfare in these animals can generate dubious results in these studies [ 44 , 45 ]. The number of sample individuals used in both farm and laboratory environments is notably higher than in other environments, such as zoos, aquariums, shelters, and pets.…”
Section: Discussionmentioning
confidence: 99%
“…We have also named as many dogs as possible, a strategy advocated by Volsche et al (2022) for future writing about research that involves animals. Naming is not a possibility unique to comics of course -they could be named in 'single-channel' mediums.…”
Section: Multimodalitymentioning
confidence: 99%
“…As just noted, Erica Fudge wrote that a key foundational concern of animal studies was representation: 'how human documents and events constructed animals' (Fudge 2022, 254). Yet in psychology there is still relatively little attention paid to if or how the lives of animals involved in animal research are depicted, historically or in the present day (Volsche et al 2022). Hank Davis and Dianne Balfour's important text on scientist-animal interaction does include accounts of psychological research (Davis and Balfour 1992), and a handful of essays and articles have extended human-animal studies type scholarship to physiology or psychology settings (Birke 2010;Despret 2004;Haraway 1989;Pettit 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several aspects of ecological assessment require whole animal approaches (e.g. phenotypic plasticity: Forsman, 2015) and inter-individual variation is an important aspect of experimental variability (Voelkl et al, 2020) that should be considered when designing (van der Goot et al, 2021a) and interpreting (Volsche et al, 2023) research. Understanding animals’ experiences of their states or conditions provides one source of information about those conditions and potential changes that would improve them.…”
Section: Introductionmentioning
confidence: 99%
“…Taking participants’ voices into account can help in the project design and evaluation, and this is true for both human participants (Dresser, 2015; Hoddinott et al, 2018; McDonald et al, 2013) and animal participants (Edelblutte et al, 2023; Johnson, 2023; Sueur et al, 2023). Improving animals’ welfare can refine protocols (Neville et al, 2023) and study validity (Brill et al, 2021; de Waal, 2016; Schaller, 2023; Würbel, 2017) and information about the welfare of animal participants should inform our evaluations and interpretations of experiments (Volsche et al, 2023). There have been questions about data from studies using methodologies that compromise animals’ welfare, such as forced swim tests in depression research.…”
Section: Introductionmentioning
confidence: 99%